Studi Komparasi Kuat Tekan Beton antara Limbah Debu dan Limbah Cutting Besi sebagai Campuran Beton - Sutantiningrum, Kartika Hapsari; Pratiwi, Devi Megarusti; Riyadi, Muhtarom (Politeknik Negeri Lhokseumawe, 2023)
Waste from iron smelting activities can be in the form of dust and pieces of iron where this waste is produced using scrap iron as raw material. This waste can replace the building blocks of concrete. In this test, the compressive strength of concrete was tested by adding a mixture of waste dust (sample A) and pieces of iron that had passed through a 1 cm sieve (sample B) on cylindrical concrete measuring 10 x 20 cm with the number of test object samples each totaling 3 at age 14 and 28 days. Tests were carried out at 14 days and 28 days of concrete using a soaking process, then drying for 24 hours and compression testing of the concrete using a compression testing machine. From the calculation results, it was found that the compressive strength value of the concrete in sample A was greater than that in sample B with the difference in compressive strength on the 14th day being 1.69 Mpa and the difference in compressive strength on the 28th day being 1.86 Mpa.Limbah aktivitas peleburan besi dapat berupa debu dan potongan besi dimana limbah ini dihasilkan dengan bahan baku besi bekas. Limbah tersebut dapat menggantikan bahan penyusun beton. Pada pengujian ini dilakukan pengujian kuat tekan beton dengan penambahan campuran limbah debu (sampel A) dan potongan besi yang telah lolos saringan 1 cm (sampel B) pada beton silinder berukuran 10 x 20 cm dengan banyaknya sampel benda uji masing-masing berjumlah 3 pada umur 14 dan 28 hari. Pengujian dilakukan pada umur beton 14 hari dan 28 hari dengan proses perendaman, kemudian dilakukan pengeringan selama 24 jam dan pengujian tekan beton dengan alat compression testing machine. Dari hasil perhitungan didapatkan nilai kuat tekan beton pada sampel A lebih besar daripada sampel B dengan selisih kuat tekan pada hari ke 14 sebesar 1,69 Mpa dan selisih kuat tekan pada hari ke 28 sebesar 1,86 Mpa.